Comparison of spectrophotometric, potentiometric and voltammetric methodologies for the determination of nitrite and nitrate in industrial effluents and in watercourses - Cherrine Kelce Pires; Efraim Lázaro Reis; Maria Isabel Cristina Batista Mayrink; Gabriel Henrique Sperandio (The Journal of Engineering and Exact Sciences)
The study addresses the importance of treating wastewater, such as water from human activities (domestic, industrial, agricultural), before it is discharged into the environment. The presence of nitrate and nitrite ions in these waters is a concern, as they are harmful to human health. The objective of this study is to evaluate different analytical techniques to measure the amount of these ions in industrial effluents and river water. The water samples were collected in Timóteo, a region with steel industries. The collections were made at three treatment points of a steel industry and at different points of the Timotinho Stream. These samples were filtered and analyzed in the laboratory using three different techniques, UV-Vis Spectrophotometry, Potentiometry with ion-selective electrodes and Differential Pulse Voltammetry. The results showed that all three techniques analyzed were effective in determining nitrite and nitrate in the water samples. However, there were some important considerations: UV-Vis spectrophotometry is quite accurate, but can be affected by interferences in the sample, such as the presence of other substances that absorb light at the same wavelength; potentiometry with ion-selective electrodes, despite being a simpler and lower-cost technique, also presented good results. Because it is more affordable, it is considered an excellent option for use in routine analyses, especially in places where resources are limited; and finally, differential pulse voltammetry, which is a more complex technique, but offers high sensitivity and can be useful in cases where very low concentrations of ions need to be detected. It is concluded that all three techniques can be used to measure nitrate and nitrite in industrial effluents and river waters, with variations in choice depending on the context. This is the main idea of ??the study: to identify effective techniques for measuring hazardous contaminants (such as nitrate and nitrite) in wastewater, choosing the most appropriate technique based on accuracy, sensitivity, and cost.